Coronary artery bypass grafting and health-related quality of life - Merkouris, Anastasios (My University, 2003)
Coronary artery bypass surgery (CABS) has traditionally been evaluated using exclusively clinical indicators such as mortality, morbidity and complication rates. Today, any objective assessment should always be supplemented with the patients' subjective asses-sement of the quality of life. Research findings suggest that almost one forth of the patients after CABS exhibit a significant improvement in the quality of life, especially in regards to physical condition and functioning. However, in the early recovery period patients frequently demonstrate psychological problems and have a limited activity. Sex, age, presence of other chronic diseases and physical condition before surgery have been found to be significant predictive factors of the quality of life after CABS. Health care professionals must understand the importance of patients' assessment of the quality of life. They must identify patients at high risk for negative outcome after CABS, plan an individualized pre and post-operative hospital care plan, and institute a rehabilitation program to meet their needs.